Performance of growth regulators on breaking dormancy and to induce early and uniform sprouting in elephant foot yam - R. Muthuraj; S. Sunitha; Saravanan Raju (JOURNAL OF ROOT CROPS, 2024)
Elephant foot yam [Amorphophallus paeoniifolius (Dennst.) Nicolson] is a popular tropical tuber crop grown for its starchy corms. It is propagated through both corms and cormels. Lack of sufficient planting materials of uniform size, non-availability of good quality planting materials and corm dormancy are the major constraints in the production of elephant foot yam. Corms are not suitable for immediate planting due to the dormancy period and also the slow development of buds which takes about 2-3 months after harvest. Field experiment was conducted at ICAR-Central Tuber Crops Research Institute (CTCRI) , Sreekariyam, Thiruvananthapuram, Kerala during crop seasons 2017-18 and 2018-19 to find out the performance of growth regulators and chemical treatments on dormancy breaking to induce uniform sprouting and enhance yield in elephant foot yam. The results revealed that the corms subjected to fumigation treatment with carbon disulphide @ 80 ml per 100 kg corm resulted in maximum uniform sprouting with 89.75%, 99.89% sprouting at 15, 40 days after planting followed by Gibberellic acid (GA3 200 ppm). The growth parameters indicated that maximum plant height (58.75cm), pseudo stem girth (86.25cm) and canopy spread (77.65cm) were recorded in plants raised from corms fumigated with carbon disulphide @ 80 ml per 100 kg corm at 90 days after planting. The corm yield data revealed that plants raised from fumigated corms produced significantly higher corm yield (34.85 t ha-1), followed by plants raised from corms treated with GA3 (200 ppm) (29.25 t ha-1), in comparison to 14.93 t ha-1 from plants raised from untreated corm. Keywords : Germination, Dormancy breaking, Fumigation, Growth regulator, Corm yield